1988
DOI: 10.1111/j.1748-5827.1988.tb02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin lesions in canine leishmaniasis

Abstract: Forty‐three dogs affected by canine leishmaniasis (CL) with skin lesions have been studied clinically and histopathologically. Identification of leishmaniads in tissues was achieved using indirect immunoperoxidase staining. According to both macroscopic and microscopic lesions, four different dermatological patterns have been observed. Twenty‐six dogs showed alopecia and desquamation as the main skin lesions. Histologically a diffuse non‐suppurative dermatitis, with numerous leishmaniads inside macrophages was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
1
28

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 3 publications
7
85
1
28
Order By: Relevance
“…As also observed in the Old World (Ciaramella et al, 1997), symptomatic cases of CVL due to L. chagasi, in America, presents clinically with anemia, emaciation, splenomegaly, local or generalized lymphadenopathy, cutaneous lesions, ocular lesions (Brito et al, 2006) weight loss, and cachexia. In the present study, dermatological entities previously described by Ferrer (1988), Ciaramella et al (1997) and Lima et al (2004) were observed. Dry desquamation associated with alopecia usually starting on the head (mainly ears and eyes-orbital) and extending to the rest of the body was observed (Ferrer 1988;Ciaramella et al, 1997).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…As also observed in the Old World (Ciaramella et al, 1997), symptomatic cases of CVL due to L. chagasi, in America, presents clinically with anemia, emaciation, splenomegaly, local or generalized lymphadenopathy, cutaneous lesions, ocular lesions (Brito et al, 2006) weight loss, and cachexia. In the present study, dermatological entities previously described by Ferrer (1988), Ciaramella et al (1997) and Lima et al (2004) were observed. Dry desquamation associated with alopecia usually starting on the head (mainly ears and eyes-orbital) and extending to the rest of the body was observed (Ferrer 1988;Ciaramella et al, 1997).…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, dermatological entities previously described by Ferrer (1988), Ciaramella et al (1997) and Lima et al (2004) were observed. Dry desquamation associated with alopecia usually starting on the head (mainly ears and eyes-orbital) and extending to the rest of the body was observed (Ferrer 1988;Ciaramella et al, 1997). In the L. infantum infection, Rallis et al (2005) also noted nasodigital hyperkeratosis and bacterial, superficial or deep pyoderma.…”
Section: Discussionmentioning
confidence: 56%
“…These cells have an important role at the ocular surface immunity (Gillette et al, 1982). Because macrophages, dendritic cells and Langerhans cells are the main APCs over Leishmaniasis (Ferrer et al, 1988), it is easy to understand the involvement of the immunogenic mechanisms on the ocular surface in events of CVL.…”
Section: Discussionmentioning
confidence: 99%
“…FERRER et al (1988) propuseram quatro padrões dermatológicos para a leishmaniose visceral canina (LV): padrão alopécico-descamativo, ulcerativo, nodular e pustular estéril. Outros sinais cutâneos freqüentemente encontrados são hiperqueratose nasodigital e onicogrifose (KOUTINAS et al, 1993).…”
Section: Introductionunclassified